Teknologi Blended Learning Mahasiswa Di Kota Batam Dengan Metode Unified Theory Of Acceptance And Use Of Technology - Hendi Sama (Universitas Negeri Medan, 2020)
In improving the education and teaching process by lecturers in tertiary institutions, learning is carried out using Blended Learning technology. Blended learning is a collaboration and / or a combination of learning that has a traditional nature (learning by doing face-to-face) and learning by utilizing technology or what is referred to as e-learning. The application of Blended Learning technology in universities in Riau Islands province has been carried out in several universities in the city of Batam. Previous research states that there are problems in the application of Blended Learning technology. This study examines how the Acceptance of Blended Learning Technology by Students in the city of Batam with the Unified Theory of Acceptance and use of Technology (UTAUT) method. In carrying out this research activity a quantitative approach is used with a causalistic explanatory research research design. The results of this study reveal that business expectations, performance expectations, social influence, and facility conditions together affect the independent variable Blended Learning Technology Acceptance. This shows that the overall acceptance of Blended Learning Technology among students has been well received